ANALISIS DAYA SAING PERUSAHAAN MELALUI KEBIJAKAN EKO-EFISIENSI DAN KINERJA KARYAWAN UNIT PRODUKSI STUDI KASUS PT. UNGGUL JAYA SEJAHTERA PEKALONGAN - Arridha Satria Rahmanandam; Dody Setyadi; Erika Devie (Politeknik Negeri Semarang, 2016)
The implementation of eco-efficiency policies still needed because environmental issues arestill a spotlight. Therefore, employees support needed until affect the improvement ofenterprises. The purpose of this thesis is to analyse the influence of eco-efficiency policies andemployee performance against the competitiveness of PT. Unggul Jaya Sejahtera Pekalongan.This thesis used questionnaire and observation as method of collecting data. Afterwards in theanalysis method used multiple linear regression analysis. The results was that there wereinfluence between eco-efficiency policies and employee performance against thecompetitiveness of PT. Unggul Jaya Sejahtera Pekalongan in the form of Y = 6,755 + 0,326X1+ 0,372X2 + e. The recommendation was PT. Unggul Jaya Sejahtera Pekalongan shouldresume eco-efficiency policies by continuing to make update and repair it with employees.